Coaching: leadership and professional development - Ortiz Luzuriaga, Daniel Hernán; Alvarez Maldonado, Johanna Andrea; Coronel Perez, Iván Ariolfo; Acosta Véliz, Marjorie Marcela (Revista Universidad de Guayaquil, 2020)
Objective: To analyze the coaching as a tool for business learning and development. Materials and methods: this research is a qualitative literature review which describes the application of coaching in business and presents results of success in practical cases. Results: Optimizing the qualities and business skills is a key factor for the achievement of targets and development of organizations. Business coaching is a tool that encourages the human resource, promoting actions change, involvement in the decision making and leadership evident in performance improvement. Conclusions: Coaching influence in the management of human talent improving performance and work climate. It is a creative and stimulating process that serves as inspiration to maximize their personal potential